The existence of waste bank management and the impact on the environment and trends of community consumption (Case study of the Ngudi Resik Waste Bank, Krecekan, Wironanggan, Sukoharjo) - Ika Feni Setiyaningrum; Asiah Wati; Suryati (Universitas Ahmad Dahlan, 2022)
The presence of a waste bank institution can encourage people to have the habit of sorting waste and change the paradigm that waste is worth. Furthermore, with a waste bank, the community can earn additional income from selling waste. The presence of a waste bank also has an impact on aspects of environmental cleanliness. In this study, researchers describe the environmental impact of the existence of a waste bank and the allocation of additional income earned by the community from the sale of sorted waste. The method used in this research is a survey by conducting interviews with the waste bank management to determine the management model. Interviews were also conducted with waste bank customers to obtain data on the amount of waste deposited and the customer's financial allocation. The number of customers in Dusun Krecekan is 19 people. Data analysis was conducted using descriptive statistical methods to describe the waste bank management mechanism and the portion of the community's additional income allocation from participation in waste bank activities. The presence of the Krecekan Ngudi Resik waste bank is the result of initiation from the community-driven by the desire to create a clean environment. Good waste bank management is the key to a sustainable waste bank. The presence and support of community leaders also play an essential role in the sustainability of the waste bank. The Krecekan Ngudi Resik waste bank has positively impacted environmental hygiene and the community's economy. Most people who become customers (78.9%) allocate money obtained from waste bank activities for consumption needs.